1989
DOI: 10.1177/070674378903400704
|View full text |Cite
|
Sign up to set email alerts
|

Focal Family Therapy Outcome Study I: Patient and Family Functioning*

Abstract: This pilot study compared the efficacy of two models of family therapy plus medication in the treatment of ten schizophrenic patients previously considered poor responders to neuroleptics alone. Focal Family Therapy (FFT), a limited psychodynamic model, was compared with Supportive Management Counselling (SMC), an educative, problem-solving approach. Family treatment was begun during admission to hospital and continued for up to six months post-discharge. Patient and family measures were administered on assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
11
0
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 18 publications
3
11
0
1
Order By: Relevance
“…The findings of this study are reported elsewhere (15) In summary, we have demonstrated that FFT was as effective as a psychoeducational approach in lowering expressed emotion and in improving the relapse rate for patients, and that patients from families treated with FFT showed a significantly more rapid improvement in symptoms than did patients treated with the psychoeducational aproach alone. The findings of this study are reported elsewhere (15) In summary, we have demonstrated that FFT was as effective as a psychoeducational approach in lowering expressed emotion and in improving the relapse rate for patients, and that patients from families treated with FFT showed a significantly more rapid improvement in symptoms than did patients treated with the psychoeducational aproach alone.…”
supporting
confidence: 74%
See 2 more Smart Citations
“…The findings of this study are reported elsewhere (15) In summary, we have demonstrated that FFT was as effective as a psychoeducational approach in lowering expressed emotion and in improving the relapse rate for patients, and that patients from families treated with FFT showed a significantly more rapid improvement in symptoms than did patients treated with the psychoeducational aproach alone. The findings of this study are reported elsewhere (15) In summary, we have demonstrated that FFT was as effective as a psychoeducational approach in lowering expressed emotion and in improving the relapse rate for patients, and that patients from families treated with FFT showed a significantly more rapid improvement in symptoms than did patients treated with the psychoeducational aproach alone.…”
supporting
confidence: 74%
“…From 1983 to 1987, we carried out a controlled outcome study that compared the efficacy of FFT with a psychoeducational approach. The findings of this study are reported elsewhere (15) In summary, we have demonstrated that FFT was as effective as a psychoeducational approach in lowering expressed emotion and in improving the relapse rate for patients, and that patients from families treated with FFT showed a significantly more rapid improvement in symptoms than did patients treated with the psychoeducational aproach alone. We also compared our data with that reported in the literature with respect to community tenure for patients.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…However, successful family interventions incorporating psychodynamic principles or techniques have been carried out in both Scandinavia and the US (e.g. Levene, Newman, & Jefferies, 1989Tuori et al, 1998), and reports have begun to appear in British psychotherapy literature reporting on successful exploratory use of psychodynamicinterpersonal interventions with people with schizophrenia (Davenport, Hobson, & Margison, 2000).…”
Section: Examples Of Investigator Allegiance From the Schizophrenia Lmentioning
confidence: 99%
“…For example, the earliest outcome research was conducted by Sigal et al (1967), attempting to determine the indicators of therapeutic outcome in conjoint family therapy. Effective research was conducted during the 1970s (Rotrock et al 1977;Ewitt 1978;Woodward et al 1978) and during the 1980s (Lebow 1981;Pevsner 1982;Levene et al 1989). No significant family therapy outcome research was conducted in the 1990s, according to the SSCI.…”
Section: Hot Research Topics and Trendsmentioning
confidence: 99%